The Effectiveness of Problem-Based Learning on the Hoax Informations to Improve Students’ Critical Thinking Skills (Related to Some Foods and Beverages) - Tri Dewi Apriyani; Noor Fadiawati; M. Mahfudz Fauzi Syamsuri (International Journal of Chemistry Education Research, 2019)
The hoax informations that spread through social media had a negative impact on society. Therefore, research had been conducted in Gedongtataan Upper Secondary School No.1  to describe the effectiveness of problem-based learning model on hoax informations in improving students' critical thinking skills. This study was used the matching only pretest-posttest control group design. The sample in this study was the 11th grade of IPA 4 (experimental class) and the 11th grade of IPA 5 (control class) which was obtained by using purposive sampling technique. The results showed that the average n-gain in the experimental and control classes was 0.7 and 0.6, respectively. Based on this, it could be concluded that the problem based learning model on the hoax informations was effective in improving students' critical thinking skills. Keywords: critical thinking skills, hoax informations, problem-based learning.